Abnormal responses of myeloid progenitor cells to granulocyte-macrophage colony-stimulating factor in human cyclic neutropenia. - Wright, D G (1989)
Granulocyte-macrophage progenitors (CFU-GM) from four patients with childhood onset cyclic neutropenia demonstrated abnormal in vitro proliferative responses to purified, recombinant human granulocyte-macrophage colony-stimulating factor (rhGM-CSF) when examined in detailed dose-response studies. Marrow aspirate specimens were obtained for these studies from cyclic neutropenia patients (both during neutropenic nadirs and during recovery phases of cycles), from leukemia patients in remission who had received myelosuppressive chemotherapy, and from healthy normal volunteers. Nucleated marrow cells were then isolated by density-gradient centrifugation and cryopreserved to permit studies of CFU-GM from patients and controls to be carried out at the same time and in replicate. Maximum clonal growth of CFU-GM from normal subjects and from individuals recovering from drug-induced myelosuppression was elicited by 20-100 pmol/liter rhGM-CSF, and the CSF concentrations that induced half-maximal responses (ED50) were between 1.0 and 3.0 pmol/liter. In contrast, maximum growth of CFU-GM from the cyclic neutropenia patients required greater than or equal to 1.0 nmol/liter rhGM-CSF and ED50's were greater than 30.0 pmol/liter. These abnormalities in the GM-CSF responsive growth of myeloid progenitors were independent of cycle time and were most apparent with the predominantly neutrophilic 7-d CFU-GM. Moreover, differences in the growth of 14-d CFU-GM could be attributed mostly if not entirely to differences in the generation of neutrophilic colonies. These findings indicate that childhood onset cyclic neutropenia is associated with an underlying disturbance in the GM-CSF responsive growth of myeloid progenitors committed to neutrophilic differentiation.